2023
DOI: 10.1021/acs.jproteome.3c00593
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics Profiling Reveals Differential Alterations after FAS Inhibition in 3D Colon Cancer Cell Culture Models

Brian D. Fries,
Fernando Tobias,
Yijia Wang
et al.

Abstract: Cancerous cells synthesize most of their lipids de novo to keep up with their rapid growth and proliferation. Fatty acid synthase (FAS) is a key enzyme in the lipogenesis pathway that is upregulated in many cancers and has gained popularity as a druggable target of interest for cancer treatment. The first FAS inhibitor discovered, cerulenin, initially showed promise for chemotherapeutic purposes until it was observed that it had adverse side effects in mice. TVB-2640 (Denifanstat) is part of the newer generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…These results show that HT-29 spheroidsan MSS, TP53 mutant colorectal cancer cell linetreated with either cerulenin or TVB-2640 are undergoing a ferroptotic death mechanism. This result agrees with the previously collected lipidomics data where it was observed that PC and PE lipids with two more degrees of unsaturation were elevated compared with controls as well as fatty acids . The decreased ability of these spheroids to scavenge lipid peroxides coupled with increased abundances of PUFA PC and PE lipids, as well as fatty acids, shows that ferroptosis is occurring within these spheroids.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These results show that HT-29 spheroidsan MSS, TP53 mutant colorectal cancer cell linetreated with either cerulenin or TVB-2640 are undergoing a ferroptotic death mechanism. This result agrees with the previously collected lipidomics data where it was observed that PC and PE lipids with two more degrees of unsaturation were elevated compared with controls as well as fatty acids . The decreased ability of these spheroids to scavenge lipid peroxides coupled with increased abundances of PUFA PC and PE lipids, as well as fatty acids, shows that ferroptosis is occurring within these spheroids.…”
Section: Discussionsupporting
confidence: 92%
“…Both HCT 116 and HT-29 spheroids were dosed with either cerulenin or TVB-2640 at their respective IC 50 concentrations . A 0 h time point was harvested and used as the control for statistical analysis and differential expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations